2022
DOI: 10.17221/106/2021-swr
|View full text |Cite
|
Sign up to set email alerts
|

The coupling of hillslope- and gully-erosion increases their controlling efforts: A case study in Liaoning Province, China

Abstract: The widespread hillslope- and gully-erosion in Liaoning Province of Northeast China, pose serious challenges to the local agricultural production. Hillslope- and gully-erosion have typically been studied separately; however, there has been little investigation on the relationship of these two types of erosion. In this study, the coupling relationship of the hillslope- and gully-erosion from the perspectives of erosion intensity and land use, as well as the slope gradient, aspect, and shape, was analysed. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…Some studies propose that vegetation cover on sunny slopes can reduce erosion by stabilizing the soil (Perreault et al, 2017). However, others argue that sunny slopes may experience increased erosion potential due to water evaporation caused by prolonged exposure to sunlight, limiting plant growth (Fan et al, 2022). Our orthophoto images indicate that herbaceous vegetation is less abundant on sunny slopes compared with shady slopes, suggesting that soil moisture evaporation is the primary factor limiting herbaceous growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies propose that vegetation cover on sunny slopes can reduce erosion by stabilizing the soil (Perreault et al, 2017). However, others argue that sunny slopes may experience increased erosion potential due to water evaporation caused by prolonged exposure to sunlight, limiting plant growth (Fan et al, 2022). Our orthophoto images indicate that herbaceous vegetation is less abundant on sunny slopes compared with shady slopes, suggesting that soil moisture evaporation is the primary factor limiting herbaceous growth.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies propose that vegetation cover on sunny slopes can reduce erosion by stabilizing the soil (Perreault et al, 2017). However, others argue that sunny slopes may experience increased erosion potential due to water evaporation caused by prolonged exposure to sunlight, limiting plant growth (Fan et al, 2022).…”
Section: Complex Effects Of Slope Aspect On Erosion and Uplift In Ter...mentioning
confidence: 99%
“…Concentrated surface runoff is one of the most important factors in the development of gullies on agricultural lands (Daba et al, 2003). Similarly, high gully length densities have been observed in concave slopes compared to convex and straight slopes in Liaoning Province, China (Fan et al, 2022).…”
Section: Predisposing Factors Affecting the Life Cycle Of Gulliesmentioning
confidence: 99%
“…Gully erosion and landslides in Eastern Nigeria arose from the geologic features and processes of the area, apart from rainfall events of high intensity [8]. Rainfall was found to be the most factor of gully erosion in Eastern and Northern Ghana [13] while [14] reported that the highest hilltop erosion amount and gully density occurred on concave slopes followed by convex and straight slopes in Liaoning Province, China. In the view of [15], the Principal Component Analysis (PCA) performed on the variables influencing gully erosion in Southeast Nigeria indicated that the level of variance explained in the yearly gully change variable was most similar to PCI (representing the component with the highest eigen value) to vegetation cover loss.…”
Section: Introductionmentioning
confidence: 99%